Acionamento do motor de corrente contínua a ímãs permanentes sem escovas utilizando estratégia a quatro chaves - Brasão, Leandro Cândido (2012)
Permanent magnet motors possess high efficiency and can be commercially competitive. The main purpose of this paper is to describe a low cost four-switch brushless dc motor drive with compensated direct current controlled our compensated hysteresis strategy. The description of the mathematical model is used in the computational simulation models to four-switch and six-switch. These results are here compared in an experimental model of drive, where the six-switch PWM drive and hysteresis drive is compared to the four-switch hysteresis compensated drive and not compensated drive. The four-switch drive has the potential to reduce costs by reducing the number of switches in commercial, industrial and residential applications.